Comparison of real-time PCR and nested PCR based on the HlyA gene for the detection of Listeria monocytogenes. Application on cheese samples - Zbrun, María Virginia; Moreno, Nadia; Camussone, Cecilia; Signorini Porchiett, Marcelo Lisandro; Primo, María Evangelina (Springer, 2024)
The aim of the present study was to compare the performance of a nested polymerase chain reaction (nPCR) and a real-time PCR based on the amplification of the HlyA gene from Listeria monocytogenes using a plasmid DNA standard. Nested PCR was developed with an internal amplification control (IAC). Both techniques were validated in soft cheese samples by comparing their results with the results of the microbiological reference method ISO 11290–1:2017. Cheese samples artificially contaminated with 3.5 to 3,500 UFC/25 g were processed by ISO 11290–1:2017 and, at several times of culture, DNA samples were extracted. All cheeses contaminated with L. monocytogenes were positive for the microbiological method 96 h post contamination and for nPCR and real-time PCR 48 h post contamination. At this time, the HlyA gene was amplified in all contaminated samples. Both molecular techniques showed the same sensitivity, 30 copies/reaction or 3.5 UFC/25 g, when plasmid DNA standard or artificially contaminated cheese samples were used. Finally, eighty soft cheese samples obtained from local retail stores and tested by three methods were negative, indicating a 100% concordance in results. The development of an nPCR with IAC reinforces the reliability of the negative results without increasing the costs of the reaction. Besides, nPCR showed less sensitivity to the presence of inhibitory substances in the reaction. The use of one of these molecular techniques could be easily coupled to the microbiological method, serving as a screening method in the food industry for hygiene monitoring and early identification of contaminated foods.